Sistem Operasi Integrasi Teknologi Augmented Reality dan Virtual Reality dalam Aplikasi Moblo dan Relax untuk Android - Rakhmadi Rahman; Andi Aulia Safirah; Anita Septiani Mustamin; Fanilda Damayanti (Fakultas Teknik Universitas Cenderawasih, 2024)
This research examines the Android operating system in the context of Augmented Reality (AR) and Virtual Reality (VR) applications with a focus on the Moblo (AR) and Relax (VR) applications. Android, as the primary operating system in mobile devices, offers a powerful and flexible platform for AR and VR application development. Moblo is an AR application that allows users to design and visualize furniture in a real space, while Relax is a VR application that provides meditation and relaxation experiences in a virtual environment. This research aims to understand how the Android operating system supports the development and operationalization of AR and VR applications, as well as evaluating the performance and user experience of these two applications. The results show that Android provides significant support for AR and VR application development, with Moblo and Relax showing good performance and providing a satisfactory user experience. However, further optimization is needed to ensure consistent performance across Android devices.